1993
DOI: 10.1111/j.1432-1033.1993.tb17885.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the topology of eukaryotic membrane proteins

Abstract: We show that the so-called 'positive inside' rule, i.e. the observation that positively charged amino acids tend to be more prevalent in cytoplasmic than in extra-cytoplasmic segments in transmembrane proteins [von Heijne, G. (1986) EMBO J. 5, 3021-30271, seems to hold for all polar segments in multi-spanning eukaryotic membrane proteins irrespective of their position in the sequence and hence can be used in conjunction with hydrophobicity analysis to predict their transmembrane topology. Further, as suggested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
172
1
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(188 citation statements)
references
References 52 publications
14
172
1
1
Order By: Relevance
“…It is believed that in this latter case, the tryptophan residue is able to control the association of the peptide with the bicelle. This result is not surprising given previous studies that have shown clustering of aromatic residues at the memebrane-water interface [43][44][45][46]. However, this result does demonstrate the power of one amino acid in dominating lipid-peptide interactions as well as the need for careful consideration when constructing putative transmembrane domains.…”
Section: Resultssupporting
confidence: 63%
“…It is believed that in this latter case, the tryptophan residue is able to control the association of the peptide with the bicelle. This result is not surprising given previous studies that have shown clustering of aromatic residues at the memebrane-water interface [43][44][45][46]. However, this result does demonstrate the power of one amino acid in dominating lipid-peptide interactions as well as the need for careful consideration when constructing putative transmembrane domains.…”
Section: Resultssupporting
confidence: 63%
“…Prediction methods were designed to predict the locations of HTMs (von Heijne, 1981(von Heijne, , 1986a(von Heijne, , 1986b(von Heijne, , 1992Argos et al, 1982;Kyte & Doolittle, 1982;Engelman et al, 1986;Cornette et al, 1987;von Heijne & Gavel, 1988;Degli Esposti et al, 1990;von Heijne & Manoil, 1990;Landolt-Marticorena et al, 1992;Donnelly et al, 1993;Edelman, 1993;O'Hara et al, 1993;Sipos & von Heijne, 1993;Jones et al, 1994;Persson & Argos, 1994;Donnelly & Findlay, 1995; and the orientation of HTMs with respect to the cell (dubbed topology, Fig. 1; von Heijne & Gavel, 1988;von Heijne, 1989von Heijne, , 1992Nilsson & von Heijne, 1990;Sipos & von Heijne, 1993;Jones et al, 1994;. If the locations of the HTMs and the topology are known with sufficient accuracy, 3D structure can be predicted successfully for the membrane spanning segments by an exhaustive search of the entire possible structure space .…”
Section: Prediction Of Htmsmentioning
confidence: 99%
“…In general, current 1D predictions are not accurate enough to provide the demanded precision in locating the helices. (2) A simple and successful technique to predict topology is the positive-inside rule (von Heijne & Gavel, 1988;Hartmann et al, 1989;von Heijne, 1989von Heijne, , 1992Boyd & Beckwith, 1990;Dalbey, 1990;Nilsson & von Heijne, 1990;Sipos & von Heijne, 1993): positively charged residues occur more often in intra-cytoplasmic than in extra-cytoplasmic regions. Applying this rule for the prediction of topology relies crucially on a correct prediction of the nontransmembrane regions.…”
Section: Are Further Improvements Of Prediction Accuracy Necessary?mentioning
confidence: 99%
See 1 more Smart Citation
“…Both proteins appeared to have membranespanning domains. The HRD3 gene encoded a protein with four features consistent with Hrd3p being a transmembrane protein oriented with the amino terminus on the lumenal site of a membrane (Sipos and von Heijne, 1993, and references therein, and Doolittle, personal communication). These features included a candidate cleavable hydrophobic N-terminal signal sequence, several asparagine-linked glycosylation consensus sites (NxT/S) in the hydrophilic region following the signal sequence, a hydrophobic region of 22 amino acids with flanking charge density and hydrophobic moment predicted for a transmembrane span, and a relatively small cytoplasmic domain with a stop-transfer sequence immediately adjacent to the transmembrane span.…”
Section: Both Hrd1 and Hrd3 Genes Encoded Novel Proteinsmentioning
confidence: 99%